(untitled) (Statistics, Optimization & Information Computing, 2026)
This study systematically reviews the current state of artificial intelligence (AI) applications in the tourism sector and their role in enhancing customer experience. It examines how AI is used to optimize operations and personalize services and explores factors that drive or hinder AI adoption. Following PRISMA guidelines, the review covers 57 articles published from 2000 to 2024, sourced from Web of Science and Scopus, based on defined inclusion criteria. The review also includes a bibliometric analysis of publication patterns and keyword co-occurrence using VOSviewer to identify prominent research themes and gaps. The analysis reveals eight thematic clusters: AI applications (e.g., demand forecasting, dynamic pricing, service automation, personalization) and associated challenges (technical, financial, socio-ethical). While AI offers significant opportunities to enhance tourism operations and customer experience, issues of data privacy, ethics, and workforce displacement remain prominent. These findings are synthesized into an integrative conceptual framework that links technological, ethical, and contextual factors influencing AI adoption. The study provides practical insights for tourism managers, highlighting the need to balance technological innovation with ethical considerations and to adapt AI strategies to diverse cultural contexts.